(untitled) (Fiep Bulletin - online, 2015)
This paper describes de data found in the research on a methodological proposal to the teaching of Rhythmic Gymnastics (RG) at the School Club of the Education Secretariat of Rio de Janeiro County. That proposal aims to stimulate the knowledge building on a motor, creative and autonomous approach, which deals with feelings, emotions and social relationship issues present in the group (and with it), starting from the problematization of its teaching.